Penegakan Hukum Pidana Perusahaan yang Tidak Memenuhi Kewajibannya dalam Program Badan Penyelenggara Jaminan Sosial - Didik Lestariyono; Bambang Sugiri; Rachmad Safa'at (University of Merdeka Malang, 2019)
There is a gap between das sollen and das sein. Das sollen (legal regulations) in Article 19 paragraph (1) and paragraph (2) jo. Article 55 of the BPJS Law provides criminal sanctions to companies that do not pay BPJS contributions to their workers. However, das sein (in fact / events that occur in the community) companies are not subject to criminal sanctions even though the criminal elements in the BPJS Law have been fulfilled. This study uses an empirical juridical method with a sociological juridical approach. The conclusions of this study are 1) Factors that cause companies not fulfilling their obligations as participants in the program due to the company's lack of discipline in managing finances which should be used as contributions to BPJS program workers and because the relevant stakeholders only provide administrative sanctions to companies. 2) The legal implication for companies is that they are subject to administrative sanctions. 3) Law enforcement efforts carried out by law enforcement officers against companies that do not fulfill their obligations in the BPJS program in Malang Regency are the imposition of criminal sanctions.How to cite item: Lestariyono, D., Sugiri, B., Safa'at, R. (2019). Penegakan Hukum Pidana Perusahaan yang Tidak Memenuhi Kewajibannya dalam Program Badan Penyelenggara Jaminan Sosial. Jurnal Cakrawala Hukum, 10(2), 156-165. doi:https://doi.org/10.26905/idjch.v10i2.3225